Polski Instytut Sztuki Filmowej – status prawny, organizacja, zadania - Czarnecki, Krzysztof; Wantoch-Rekowski, Jacek (PRAWO i WIĘŹ, 2024)
The paper contains an analysis of legal matters concerning the Polish Film Institute. In analysing the Institute’s legal status, the authors have focused primarily on the provisions of the Constitution of the Republic of Poland, the Public Finance Act, the Cinematography Act and the Institute’s Statute. The Institute, being a state legal person, is a unit of the public finance sector. The authors examine issues relating to the organisation of the Institute and the tasks it performs.